Beyond Scientism and Skepticism: An Integrative Approach to Global Mental Health - Dan J Stein; Judy eIlles (Frontiers in Psychiatry, 2015)
The global burden of disorders has shifted from infectious disease to non-communicable diseases, including neuropsychiatric disorders. Whereas infectious disease can sometimes be combated by targeting single causal mechanisms, such as prevention of contact-spread illness by hand-washing, in the case of mental disorders multiple causal mechanisms are relevant. The emergent field of global mental health has emphasized the magnitude of the treatment gap, particularly in the low and middle income world, and has paid particular attention to upstream causal factors, for example, poverty, inequality, and gender discrimination in the pathogenesis of mental disorders. However, this field has also been criticised for relying on erroneous Western paradigms of mental illness, which may not be relevant or appropriate to the low- and middle-income context. Here, it is important to steer a path between scienticism and skepticism. Scientism regards mental disorders as essential categories, and takes a covering law approach to causality; skepticism regards mental disorders as merely social constructions, and emphasizes the role of political power in causal relations. We propose an integrative model that emphasizes the contribution of a broad range of causal mechanisms operating at biological and societal levels to mental disorders, and the consequent importance of broad-spectrum and multi-pronged approaches to intervention.